Globalizacijos įtaka miestams ir jos optimizavimo urbanistinės galimybės Kauno centre - Kamičaitytė-Virbašienė, Jūratė; Gražulevičiūtė-Vileniškė, Indrė (Journal of Architecture and Urbanism, 2008)
Influence of globalization on cities and urbanistic possibilities of its optimization in Kaunas city centerGlobalization, prevailing trend of development of contemporary societies, inevitably influences visual and social aspects of cities. Changes of cities influenced by globalization are usually associated with increasing uniformity of residential environment, decline of public spaces, fragmentation and commercialization of urban environment. Decline of traditional territorial communities, suburbanization, gentrification, and stratification are also observed in urban societies. These processes not only influence quality of life in urban territories, but also their visual characteristics. Changes of urban environment and societies influenced by globalizing processes strongly affect city’s historic environment. Striving towards sustainable development of cities it is necessary to analyze the impacts of globalization on urban environment, historic centers and districts and to search for possibilities to use its social and economic benefits and to avoid its negative influence on city’s identity and society. The influence of globalizing processes on cities, their historic environment and societies is discussed in the paper and the proposed model for optimization of the influence of globalization on historic environment with urban design means is presented. The proposed model is applied to Kaunas historic center.Article in Lithuanian.Santrauka. Ryškiausia visuomenių vystymosi tendencija tapusi globalizacija akivaizdžiai veikia miestų vaizdą ir visuomenes. Globalizuojančių veiksnių paskatinti miestų pokyčiai dažniausiai susiję su gyvenamosios aplinkos vienodėjimu, erdvių fragmentacija ir komercializacija. Miestų visuomenėse pastebimi tradicinių teritorinių bendruomenių nykimo, suburbanizacijos, gentrifikacijos ir išsisluoksniavimo procesai, turintys įtakos ne tik gyvenimo kokybei miestuose, bet ir jų vaizdui. Šie miestų ir visuomenių pokyčiai ryškiausiai pasireiškia per šimtmečius susiformavusiose istorinėse miestų dalyse. Siekiant darnaus miestų vystymosi, svarbu analizuoti globalizuojančių veiksnių įtaką miestams ir jų istorinėms dalims, ieškoti galimybių pasinaudoti šių veiksnių teikiama socialine-ekonomine nauda ir išvengti neigiamo jų poveikio miestų savitumui ir visuomenėms. Analizuojama globalizuojančių veiksnių įtaka miestams, jų istorinėms dalims ir visuomenėms, pateikiamos galimos globalizacijos įtakos optimizavimo istorinėje aplinkoje urbanistinės priemonės Kauno istorinio centro pavyzdžiu.Reikšminiai žodžiai: globalizacija, istorinė aplinka, kultūros paveldas.First Published Online: 22 May 2013